ertumbuhan Bibit Kopi Liberika Tungkal Jambi (Coffea liberica W. Bull ex Hiern) pada Media Gambut yang Diberi Kapur Dolomit - Yuyun Riyani; Y. G. Armando; Yatrofa Yatrofa (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2020)
offee is one of the leading commodities in the plantation sector which is widely cultivated in Indonesia. The aims of this research is to know the response of dolomite dosage for growth of liberica coffee seedlings in peat soil. Completely Randomized Design (RAL) were used in this research with a dolomite dose as a treatment factor. The treatment were without dolomite (control), dolomite 7.5 g / polybag, dolomite 11.25 g / polybag and dolomite 15 g / polybag. This research was conducted from June to September 2017. The results showed that giving of dolomite can increase the growth of coffee seedlings of liberica Tungkal Jambi and dolomite dosage of 7.5 g / polybag showed the best growth in performance of coffea seedlings of the whole aspect.